Dr. A. Q. Khan on Pakistan bomb - Khan, A. Q. (Abdul Qadeer), 1936-2021.; Sreedhar (New Delhi : ABC Pub. House, 1987)
Transcript of interviews, articles, and letters of a nuclear scientist from Pakistan.
Includes index.
Koleksi Sumbangan : Zainal Abidin Abdul Wahid.
Keywords: Nuclear weapons -- Pakistan; Uranium enrichment; Nuclear energy -- Government policy -- Pakistan